2014
DOI: 10.1002/stem.1578
|View full text |Cite
|
Sign up to set email alerts
|

WKYMVm-Induced Activation of Formyl Peptide Receptor 2 Stimulates Ischemic Neovasculogenesis by Promoting Homing of Endothelial Colony-Forming Cells

Abstract: Endothelial colony-forming cells (ECFCs) are recruited to the sites of ischemic injury in order to contribute to neovascularization and repair of injured tissues. However, therapeutic potential of ECFCs is limited due to low homing and engraftment efficiency of transplanted ECFCs. The Gprotein-coupled formyl peptide receptor (FPR) 2 has been implicated in regulation of inflammation and angiogenesis, while the role of FPR2 in homing and engraftment of ECFCs and neovascularization in ischemic tissues has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 48 publications
(45 reference statements)
5
73
0
Order By: Relevance
“…Human outgrowth endothelial cells (OECs) were isolated from human umbilical cord blood as previously described [12]. Cells were seeded on to the gelatin coated tissue culture plate (Millipore, Embryomax Ò , Ultrapure water with 0.1% gelatin) and maintained with endothelial cell basal medium-2 (EBM-2; Lonza, Walkersville, MD) supplemented with EGM™-2 singleQuots Ò except hydrocortisone.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Human outgrowth endothelial cells (OECs) were isolated from human umbilical cord blood as previously described [12]. Cells were seeded on to the gelatin coated tissue culture plate (Millipore, Embryomax Ò , Ultrapure water with 0.1% gelatin) and maintained with endothelial cell basal medium-2 (EBM-2; Lonza, Walkersville, MD) supplemented with EGM™-2 singleQuots Ò except hydrocortisone.…”
Section: Cell Culturementioning
confidence: 99%
“…Recently, several studies identified that the synthetic peptide WKYMVm (Trp-Lys-Tyr-Met-Val-D-Met-NH2) can induce angiogenesis of endothelial cells via FPR-2 dependent stimulation of proliferation, migration, tube formation, and sprouting activity [10,11]. In addition, a recent study reported that the WKYMVm-induced activation of FPR-2 plays a role in ischemic tissue regeneration and neovascularization by homing and angiogenic activation of outgrowth endothelial cells (OECs) [12]. However, therapeutic activities of injected peptides may be diminished by several factors, including that of rapid degradation and secretion by the circulation system.…”
Section: Introductionmentioning
confidence: 99%
“…ECFCs have shown promise for tissue regeneration. In mouse vascular injury models, they are rapidly recruited to the site of vascular injury or tissue ischemia after intravenous injection, where they initiate a vasculogenic response 8 , and they have been reported to enhance vascular repair and improve blood flow after myocardial infarction 9 , stroke 3,10 , ischemic retinopathy 2 and ischemic limb injury 8,11 , and to engraft and re-endothelialize denuded vascular segments or implanted grafts 12 . In elderly patients and subjects with peripheral arterial disease (PAD) and critical limb ischemia, ECFCs may become prone to replicative senescence, reducing their reparative potential.…”
mentioning
confidence: 99%
“…Generally, stem cells are undifferentiated cells, with known proliferation potential, being able to self-renovate and differentiate in many lineages. This is why these cells have been appointed as a hope of cure for many diseases, especially concerning tissue regeneration [55][56][57]. Stem cells carry different features, depending on the moment of their harvesting.…”
Section: Stem Cellsmentioning
confidence: 99%